Investigation of a novel multifunctional roof panel for hybrid photovoltaic/thermal/daylight application in atrium and large green house - Yu, Xu (2015)
Daylight is an energy efficient solution for illumination and visual comfort in buildings. However, successful daylight design requires effective daylight control technology to eliminate the negative impact such as overheating, unbalanced indoor daylight distribution and glare. With this mind, the current thesis presents a novel multifunctional roof panel which might be applied in atrium and large green house. The working principle of the panel is based on the non-imaging low-concentration solar collector: dielectric Compound Parabolic Concentrator (CPC). Detailed study on the dielectric CPC has found that there would be some light escaping from side wall of CPC when the incident light is beyond CPC acceptance angle, which could actually be used for indoor daylight provision; while the incident light concentrated on the base of CPC could be used for concentrating PV application. Thus a dielectric CPC panel which consists of several trough dielectric CPC rods is designed and manufactured, its function of hybrid PV/Daylight is investigated through PHOTOPIA simulation and outdoor testing, both simulated and measured results showed that under sunny condition, only 10-15% of light could be transmitted through the panel in cooling season, and the rest of the light is used for concentrating PV application; while light transmittance of about 40-60% is achievable in winter period, when daylight is desired. Additionally, constant light transmittance of about 40% is achievable under overcast sky. The above figures could verify the seasonal daylight control ability of the panel. On the other hand, for the designed panel, the rejected heat on PV could still flow into the building. As a result, a PV/Thermal system is designed to remove the rejected heat on PV cell and reutilize it for thermal application such as food drying. The design parameter such as approach velocity, pitch distance, and perforation porosity are numerically investigated by CFD simulation. The prototype of the system is built and measured under solar simulator and real sky. Both simulated and measurement results showed that the heat recovery efficiency could be 40-80% depending on different geometries and approach velocities; and little amount of rejected heat could transfer from the PV cell to the building interior. The hybrid PV/Thermal application seems to be achievable. Lastly, the energy and economic performance for the EW-orientated dielectric CPC panel is investigated using new proposed concept of “inner south projection angle” and its correlation with the CPC optical performance, the building energy simulation software EnergyPlus and its weather data are also employed. An example case on an educational building with a central atrium in Nottingham shows that: compared to the conventional double glazing window, there is 55% increase in useful daylight illuminance (500-2000lux) percentage; 81.5% reduction in window solar heat gain in cooling season and only 10.78% reduction in window solar heat gain in heating season; there is also a power generation of 290.65W/m2 from PV cells; and the estimated payback period is less than 5 years. Therefore, the proposed multifunctional roof panel for PV/Thermal/Daylight application could comprehensively utilise the solar energy and provide comfort thermal and visual indoor environment.